Giving Question Getting Answer Berbantuan Media QnA Card Terhadap Kemampuan Berpikir Kritis Siswa Materi Menghargai Keberagaman - Dzulhijjah, Annisa Nurul; Fanny, Arif Mahya (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study aims to examine the effect of the Giving Question Getting Answer (GQGA) strategy supported by QnA Card media on students’ critical thinking skills in the topic of Appreciating Diversity among fourth-grade students at SD Antawirya. The research was motivated by the low level of students’ critical thinking skills, the limited use of media during learning, and the lack of effective teaching strategies in the classroom. A quasi-experimental method with a Nonequivalent Control Group Design was employed. Data were collected using pre-tests and post-tests, and analyzed through a t-test. The participants were 53 fourth-grade students divided into experimental and control groups. The results showed that the average pre-test score of the control group was 50.2, while the experimental group scored 58.21. After the intervention, the post-test average increased to 65 in the control group and 70.36 in the experimental group. The effect size analysis yielded a value of 0.999, which falls into the high category. Therefore, the GQGA strategy supported by QnA Card media is proven to be effective in enhancing students' critical thinking skills in learning to appreciate diversity.